Problematika Guru Akidah Akhlak dalam Pelaksanaan Pembelajaran pada Kurikulum Merdeka Belajar di MTsN 01 Kota Pariaman - Nola Ariesta Elvan; Sasmi Nelwati; Misra Misra (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This research aims to examine the implementation of the Independent Learning Curriculum and the problems experienced by moral belief teachers in implementing the independent curriculum in schools, as well as the factors that influence it, and the efforts of educators in overcoming these problems. This research uses descriptive qualitative methods with data collection in the form of participant observation and interviews. The results of this research indicate that the implementation of the Independent Learning Curriculum is going well. There are also various methods and varied learning models used by educators, used with training support for educators. However, there are also obstacles such as limited teaching resources, inadequate training, and resistance to change that still need to be overcome. So there are problems that become obstacles for teachers in schools, namely first the lack of supporting media in learning, second the lack of ability to use technology, third the lack of time allocation for project-based learning. The solution that must be taken by teachers in facing the problems of implementing the independent curriculum is that the efforts applied by teachers in overcoming the problems of implementing the Independent Learning Curriculum are regular meetings with the KKG, PMO assistance, namely regular meeting activities carried out by committees in schools such as principals, educators and supervisors. school. Students continue to make projects at home, take notes, and educators take part in curriculum implementation training.